Mengembangkan Minat dan Kemampuan Bahasa Inggris Remaja di Lingkungan Bappeda Kota Tebing Tinggi - Ramadhan Damanik; Husni Thamrin (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
The problems that children face today are related to learning in pandemic times like these. Children ranging from high school to high school have difficulty learning English. Besides that English is not the everyday language that makes them strangers use it, English is also considered to be a difficult language. It's happening in many places where a lot of parents can't afford or want to enroll their children in English courses, like children in the BAPPEDA High Hill neighborhood. They want to understand and master English because English is an international language. In this practice I as a practitioner helped develop the interest and ability of the English language in teenagers who are in the BAPPEDA neighborhood. The solutions offered in the practical activities of the appropriate intervention program are used in this problem, namely micro intervention by Skidmore (Adi, 2013), case work consisting of stages such as Engagement, Intake and contract, Assessment or Program Planning, Intervention, Evaluation, and Termination. By using Skidmore's method, it's easier to practice solving client problems. The results of this activity aim to make the youth in this BAPPEDA neighborhood more confident, able to compete and not lag behind other teens on English language skills